Pathogenesis of domestic pigs submitted to mycobacterial sensitizations previous to experimental infection with Mycobacterium bovis - Cuerda, Maria Ximena (2022)
Aim of study: To demonstrate the virulence of a Mycobacterium bovis local pig isolate in order to contribute to a better understanding of the pathological and immunological consequences of M. bovis infection in previous sensitized animals. Area of study: Buenos Aires, Argentina Material and methods: One group of ten pigs received two oral doses of killed M. bovis suspension and a comparative intradermal tubercu-lin test (CIT) (multiple sensitized) and then was infected with the M. bovis strain. Another group only received the CIT (single sensitized) and the infective dose. Humoral immune response was followed monthly, and gross pathology, histopathological and bacteriological analysis were performed at necropsy 100 days after infection. Main results: M. bovis oral infection induced lesions and allowed bacterial growth in most of the animals. Previous sensitization with killed M. bovis suspension slightly raised the intensity of the response, as the multiple sensitized group showed higher lesion scores and humoral response. Research highlights: Although the differences in lesion scores were not statistically significant, oral route infection after sensitization can modify the course of infections towards a fast development of lesions with a higher fibrotic component suggestive of increased resistance to infection in the right conditions.